Corn Cropping Systems in Agricultural Soils from the Bajio Region of Guanajuato: Soil Quality Indexes (SQIs) - Alejandra Sánchez-Guzmán; Héctor Iván Bedolla-Rivera; Eloy Conde-Barajas; María de la Luz Xochilt Negrete-Rodríguez; Marcos Alfonso Lastiri-Hernández; Francisco Paúl Gámez-Vázquez; Dioselina Álvarez-Bernal (Applied Sciences, 2024)
Agriculture is a sector of great importance for Mexico’s economy, generating employment and contributing significantly to the country’s gross domestic product. The Bajio stands out as one of the most productive agricultural regions in Mexico. However, intensive agricultural practices in this area have caused a progressive deterioration and loss of soil fertility. This study focused on evaluating the quality of soils used for agriculture in the Bajio region of the State of Guanajuato, Mexico. This evaluation, utilised soil quality indexes (SQIs) based on a total of 27 physicochemical, biological and enzymatic indicators. These indicators were selected by means of a principal component analysis (PCA), which allowed for the identification of a minimum set of data. The SQIs developed in this study categorised soils into different quality levels, ranging from low to high, mainly based on the values observed in the biological indicators (SMR and qCO2), which comprised the established SQIs. The inclusion of these biological indicators provides the developed SQIs with greater sensitivity to detect minor disturbances in agricultural soils due to human activity, compared with SQIs consisting only of physicochemical indicators. The developed SQIs can be used to ensure high-quality food production in soils used for corn cultivation under similar conditions, both nationally and internationally.